Natural resources, manufacturing and institutions in post-Soviet countries. (December 2016) - Horváth, Roman; Zeynalov, Ayaz
Abstract: We examine the effect of natural resource exports on economic performance during the 1996–2010 period in the 15 independent countries that formerly comprised the Soviet Union. After the fall of communism, these countries began to demonstrate marked differences from one another with respect to economic development and institutions, which has resulted in unique cross-sectional and time variation. Using several panel regression models that address endogeneity and clustering issues, our results suggest that natural resources crowd out manufacturing unless the quality of domestic institutions is sufficiently high. Abstract : Highlights: We examine the natural resource curse in post-Soviet countries. Panel data accounting for endogeneity are used. Natural resources crowd out manufacturing sector unless the quality of domestic institutions is sufficiently high.